Professional Development of EFL Teachers at Madrasah Aliyah - Umar - Umar (STIBA IEC JAKARTA, 2022)
Professional development of EFL Teachers is seen as a way to maintain and enhance the quality of teachers. The acquired knowledge does not only bring about improvement in the teaching process, but also leads to career growth. This study uses a qualitative research method with a descriptive approach, which describes the situation as it is about an indication, or the state of the findings in the field. This article discusses the concept of professional development in the field of EFL teaching which is distinctive from ESL and other subjects. The emphasis of the article is on what are the principles of professional teachers’ development, principles of effective teachers, the difference ESL from EFL, and various programs of development they can use to improve themselves continually